2017
DOI: 10.1039/c7nr02193c
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria-targeting near-infrared light-triggered thermosensitive liposomes for localized photothermal and photodynamic ablation of tumors combined with chemotherapy

Abstract: Lonidamine, an anticancer drug that acts on mitochondria, has poor water solubility. Mitochondria are the primary source of cellular reactive oxygen species (ROS), which are necessary for photodynamic therapy. Hence, a mitochondria-targeting drug delivery system loaded with Lonidamine and a ROS-produced photosensitizer could improve the bioavailability of Lonidamine and maximize photodynamic therapeutic efficiency. Here we report, for the first time, new IR-780 and Lonidamine encapsulated mitochondria-targetin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(60 citation statements)
references
References 42 publications
0
59
0
Order By: Relevance
“…8 Importantly, cancer cells have a more hyperpolarized mitochondrial membrane potential (DJ m ) in comparison with normal cells, which makes the uptake of cationic drugs into the cancer cells more favorable. 9 As a result, targeting of mitochondria has emerged as an attractive strategy for efficient and selective cancer chemotherapy. 10,11 Recently, a lipophilic near-infrared (NIR) heptamethine dye, IR780, has been shown to have promising anticancer characteristics that acts on mitochondria.…”
Section: Introductionmentioning
confidence: 99%
“…8 Importantly, cancer cells have a more hyperpolarized mitochondrial membrane potential (DJ m ) in comparison with normal cells, which makes the uptake of cationic drugs into the cancer cells more favorable. 9 As a result, targeting of mitochondria has emerged as an attractive strategy for efficient and selective cancer chemotherapy. 10,11 Recently, a lipophilic near-infrared (NIR) heptamethine dye, IR780, has been shown to have promising anticancer characteristics that acts on mitochondria.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, this liposome upon NIR laser irradiation mediated a synergistic PTT/PDT/chemotherapy, greatly inhibiting the growth of human cervical HeLa tumors in living nude mice. Similarly, Cui’s group developed a mitochondria-targeting photothermal responsive liposome via self-assembly of triphenylphosphine (TPP)-coupled DSPE-PEG, DPPC, 1,2-distearoyl-sn-glycero-3-phosphocholine (DSPC), cholesterol, a photosensitizer (IR-780) and lonidamine (LON) [ 61 ]. TPP-binding improved the internalization of the liposome into mitochondria of cancer cells.…”
Section: Photothermal Responsive Ddssmentioning
confidence: 99%
“…65 Mitochondria in cancer cells show greater susceptibility than those in normal tissues. Thus, there is the potential to deliver radiosensitizers, 66 photosensitizers, 67 and theranostics 68 to the mitochondria of cancer cells, aiming at ROS production and oxidative stress, which induce mitochondrial permeability transitions and fundamentally affect the energy supply of cancer cells. All of the above have demonstrated that mitochondria targeting is of great significance for improving antitumor therapy.…”
Section: Mitochondria Targetingmentioning
confidence: 99%